Thiolate-Initiated Metal-Free Synthesis of Cyclopentenones via a Halogen-Stabilized Vinyl Carbanion - Umlauf, Lea Sophie; Wölper, Christoph; Haberhauer, Gebhard (Synlett, 2025)
A metal-free synthesis of cyclopentenones is described. The mechanism proceeds via a halogen-stabilized carbanion generated by the nucleophilic attack of a thiolate on a haloalkyne moiety. The sp2-hybridized carbanion undergoes cyclization to an embedded ester carbonyl, yielding the cyclopentenone. The reaction exhibits a broad tolerance toward functional groups and proceeds under mild conditions.
Keywords: Metal-free; Cyclization; sp2-Hybridized intermediate; Vinyl-carbanion; Halogen-stabilized carbanion; Cyclopentenone; Haloalkyne